Optimalisasi Recovery Oli Bekas terhadap Efektifitas Zeolit Menggunakan Metode Qualiser - Sari, Santi ; Abrina Anggraini, Sinar Perbawani (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2018)
Oil is a chemical used in motorized vehicles that is useful for reducing wear on the engine. The main use of oil is found in engine oil. Generally the oil consists of 90% base oil and 10% additional substances. In the actuating system when the engine is turned on the moving engine will occur friction on the metal which will cause the release of particles from the event. In this situation where the metal that releases the particle is usually called wear on the machine. This will cause health effects such as damage to the respiratory system, damage to the skin and carcinogenic effects (drivers of cancer). Therefore, to overcome this, we need a technology that can manage used oil, one of which is using qualiser technology. The purpose of this study was to determine the characteristics of oil waste and the feasibility of the qualifier method in achieving good oil results in the optimization process of used oil separation. The variables used are at temperatures (100-150?C) at 30, 45, 50 minutes. The research parameters are% yield, missing components and performance on the device. So the results showed that the highest% yield was 5.295% and the lowest was 0.648%, the highest and lowest missing component was 99.83%.